Spelling acquisition in a consistent orthography: The facilitatory effect of syllable frequency in novice spellers - Iaia, Marika; Marinelli, Chiara Valeria; Vizzi, Francesca; Angelelli, Paola (PLOS ONE, 2022)
This study investigates the effects of two sublexical variables, syllable frequency, and word length, in the spelling acquisition of novice spellers dealing with a transparent orthography, such as Italian. Two groups of 1 st-grade Italian children were tested respectively after 4 and 8 months of schooling, with a spelling-to-dictation task of single words created ad hoc by manipulating syllable frequency orthogonally (high vs low frequency of the first syllable) and length (short vs long words). The results show that after only four months of schooling, children could offset their difficulty in writing long words by taking advantage of the high frequency of the initial syllable. However, the regularity of Italian spelling makes it easy to capture fine-sized phoneme-to-grapheme units, rendering the syllable effect no longer detectable in more schooled children.